Altered protein expression of membrane transporters in isolated cerebral microvessels and brain cortex of a rat Alzheimer's disease model - Puris, Elena; Auriola, Seppo; Petralla, Sabrina; Hartman, Robin; Gynther, Mikko; Lange, Elizabeth Cunera Maria de; Fricker, Gert (Neurobiology of disease, 2022)
There is growing evidence that membrane transporters expressed at the blood-brain barrier (BBB) and brain parenchymal cells play an important role in Alzheimer's disease (AD) development and progression. However, quantitative information about changes in transporter protein expression at neurovascular unit cells in AD is limited. Here, we studied the changes in the absolute protein expression of five ATP-binding cassette (ABC) and thirteen solute carrier (SLC) transporters in the isolated brain microvessels and brain cortical tissue of TgF344-AD rats compared to age-matched wild-type (WT) animals using liquid chromatography tandem mass spectrometry based quantitative targeted absolute proteomic analysis. Moreover, sex-specific alterations in transporter expression in the brain cortical tissue of this model were examined. Protein expressions of Abcg2, Abcc1 and FATP1 (encoded by Slc27a1) in the isolated brain microvessels of TgF344-AD rats were 3.1-, 2.0-, 4.3-fold higher compared to WT controls, respectively (p < 0.05). Abcc1 and 4F2hc (encoded by Slc3a2) protein expression was significantly up-regulated in the brain cortical tissue of male TgF344-AD rats compared to male WT rats (p < 0.05). The study provides novel information for the elucidation of molecular mechanisms underlying AD and valuable knowledge about the optimal use of the TgF344-AD rat model in AD drug development and drug delivery research.